CIPM Certified Information Privacy Manager All-In-One Exam Guide - Gregory, Peter H. (McGraw-Hill Education, 2021)
This self-study guide covers every topic on the Certified Information Privacy Manager exam Take IAPP's rigorous Certified Information Privacy Manager (CIPM) exam with complete confidence using the comprehensive information contained in this highly effective study guide. The book enhances candidates' abilities to design, build, and run information privacy management programs. Written by a security and privacy expert and experienced author, CIPM Certified Information Privacy Manager All-in-One Exam Guid e is based on proven pedagogy and thoroughly prepares candidates to pass this exam. Beyond exam preparation, the guide also serves as a valuable on-the-job reference. •Provides 100% coverage of all eight objectives for the CIPM exam •Online content includes 300 practice questions in the Total Tester exam engine •Written by a security and privacy expert, educator, and experienced author.